Design of Low Noise Amplifier for IEEE Standard 802.11b Using Cascode and Modified Cascode Techniques. (2016) - Prameela, B.; Daniel, Asha Elizabeth
Abstract: This paper presents the performance comparison of two Low Noise Amplifiers (LNA), a basic Cascode and a modified cascode LNA for IEEE 802.11b protocol, WLAN. A modified cascode LNA with dual Common source transistors is designed and the performance parameters are compared with a designed basic cascode stage. The modified cascode stage has a high gain of 19.2dB and an optimized noise figure of 0.416dB at 2.4 GHz and at a supply voltage of 1.8V. The S11 is -13.74dB, S22 is -0.87dB and S12 is -43.63dB. The P1dB is -18.35dBm and the IIP3 is -8.42dBm. The LNA is designed to be stable over 2-3 GHz range. The power consumption of the circuit is 8.1mW. The modified cascode LNA is having around 10% improvement in gain and a 40% reduction in noise figure compared to the basic Cascode LNA. The simulations are done in cadence virtuoso Spectre RF using 180 nm technology.